Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Good Corporate Governance Terhadap Pengungkapan Corporate Sosial Responsibilty Dan Dampaknya Terhadap Abnormal Return Pada Perusahaan LQ45 - Putri Frisca Kuncorowati; Muhammad Miqdad; Ahmad Roziq (ITB AAS INDONESIA, 2021)
This study examines the effect of Profitability, Company Size, GCG on CSR disclosure and its impact on abnormal returns. The purpose of this study was to analyze the effect of Profitability, Company Size, GCG on abnormal returns and the indirect effect on CSR disclosure. The sample in this study was the LQ-45 company listed on the IDX in 2020. Data analysis used Path Analysis. The results of the path analysis study have directly shown that profitability, company size, GCG has a significant effect on CSRD with sig results less than 0.05. Meanwhile, the results of research using path analysis indirectly show that CSR disclosure is not able to strengthen the relationship between profitability, company size, GCG on abnormal returns.